LIFELONG LEARNING PERSPECTIVE AND STUDENT PERCEPTIONS IN COMPARING HOMEWORK AND HOME-LEARNING (E Conference Zone, 2022)
Regarding the importance of homework, neither instructors nor students seem to agree. While some contend that it is crucial for enhancing learning, others assert that it is often useless and harmful to one's quest for general learning. This paper encourages a switch from homework to home learning based on the ideas of lifelong learning, with a focus on the latter. I'll make the case that this strategy better equips students to partake in meaningful learning experiences throughout their whole lives, not just during their college studies. The purpose of this study was to examine the importance of student variables related to homework (such as intrinsic motivation for homework, perceived utility of homework, attitude toward homework, time spent on homework, and time management) and context (such as teacher feedback on homework and parental support for homework) in predicting approaches to homework.